Responsible leadership in projects insights into ethical decision making - Clarke, Nicholas 1966-; D'Amato, Alessia; Higgs, Malcolm; Vahidi, Ramesh (Project Management Institute, Inc., 2018)
From the publisher: Until now, there has only been a shallow understanding of how the leadership actions of project managers interact with ethics and social responsibility. Empirical research into this subject has been sparse. Responsible Leadership, by Nicholas Clarke, Alessia D'Amato, Malcolm Higgs, and Ramesh Vahidi is the first study to investigate how the relationships among managers, team members, and other stakeholders can bring about personal and ethical conflicts that impact decision making. In this groundbreaking book, the authors explore how those who serve as leaders on projects can exercise their roles in ways that respond to the ever-increasing need for ethical decision making. They examine the factors that enable and constrain responsible leadership, looking at the issues faced by project managers as they interact with team members and other stakeholders. Responsible Leadership also provides new insights into how project managers view the moral implications of conflicts that occur as they conduct their work and is a valuable addition to the project management toolkit.